Hemolytic activity and production of germ tubes related to pathogenic potential of clinical isolates of Candida albicans - M.F. Negri; M.G. Faria; E. Guilhermetti; A.A. Alves; C.R. Paula; T.I.E. Svidzinski (São Paulo State University (UNESP), 2010)
We assessed the virulence factor profile and in vitro antifungal susceptibility of 27 hospital isolates of C. albicans; 19 of these were from infections (16 urinary and three blood), and the other eight were isolated from sites of colonization (two from hands of health professionals, and six from central venous catheters). The virulence factors assayed were germ tube formation and production of extracellular products (hemolysins, proteinases, and phospholipases). Susceptibility to fluconazole, itraconazole, voriconazole and amphotericin B was determined by E-test. Regarding the virulence factors, the infection isolates produced significantly more hemolysin and germ tubes than the colonization isolates (p<0.05). There were no significant differences in the production of other factors between isolates from the two sources (p>0.05). Amphotericin B showed the lowest minimum inhibitory concentrations for all the isolates. The highest resistance was observed for the azoles, especially in the clinical isolates. These results suggest that the capacity of C. albicans to produce hemolysins and germ tubes may be associated with its pathogenic potential. Colonization isolates may pose a high risk of nosocomial infection, especially when the yeasts show resistance to antifungals.